The Influence of Digital Marketing and Service Quality on Consumer Preferences for Coffee Shops in Malang City - Prasetio Utomo; Fatasya Aulya Ngindana Zulfa; Fitriyah; Barianto Nurasri Sudarmawan (Peradaban Journal of Economic and Business, 2023)
The coffee shop industry has experienced heightened competitiveness, propelled by the consistent growth in coffee consumption and production. Evolving beyond mere purveyors of coffee, these establishments have become significant social hubs, especially among student communities. This study aims to explore the impact of digital marketing and service quality on consumer preferences within the coffee shop landscape in Kota Malang, Indonesia.. The evaluation of service quality employs the "SERVQUAL" theory, encompassing five dimensions, while digital marketing, utilizing technology and social media for product promotion, is grounded in the 4P theory. Employing nonprobability sampling, the study gathered responses from 162 participants aged 12-27 residing in Malang City, frequenting various coffee shops. Utilizing the Smart PLS 3.0 program, the data underwent rigorous analysis, passing validity, reliability, normalcy, linearity, and multicollinearity tests. The study investigates the influence of digital marketing (X1) and service quality (X2) on customer preferences through path analysis (Y). The findings indicate that both digital marketing and service quality exhibit partial yet significant effects on customer preferences. Simultaneously, when considered together, these variables exert a noteworthy positive influence on customer preferences, with service quality emerging as the most impactful determinant.